2013
DOI: 10.1177/0300060513477005
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy does not improve lung function in asthma: A meta-analysis of randomized controlled trials

Abstract: Objective: To assess the efficacy of statins in the treatment of asthma. Methods: Electronic databases were searched to identify randomized controlled trials that measured the efficacy of statins in the treatment of asthma, and a meta-analysis of the pooled data was performed. Results: Five trials were identified; four met the inclusion criteria (total number of patients 200). Compared with controls, patients in the statin groups had higher forced expiratory volume in 1 s (FEV 1 ) values before inhaled cortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…A meta-analysis in asthmatic patients on statins and those who are not on statins reported a morning rise in PEFR in statin users but this change was not statistically significant. [ 21 ] In the present study, a statistically significant increase ( P = 0.04) in PEFR was observed in rosuvastatin group. Echocardiogram evaluation of sPAP showed a small improvement in rosuvastatin group which was not statistically significant ( P = 0.07).…”
Section: Discussionsupporting
confidence: 59%
“…A meta-analysis in asthmatic patients on statins and those who are not on statins reported a morning rise in PEFR in statin users but this change was not statistically significant. [ 21 ] In the present study, a statistically significant increase ( P = 0.04) in PEFR was observed in rosuvastatin group. Echocardiogram evaluation of sPAP showed a small improvement in rosuvastatin group which was not statistically significant ( P = 0.07).…”
Section: Discussionsupporting
confidence: 59%
“…Current evidences from clinical studies have shown a decrease in systemic inflammation after treatment with oral SV in hypercholesterolemia and cigarette smoke-induced COPD patients (9,10). However, a meta-analysis of randomised controlled trials have found otherwise demonstrating that statins did not improve lung function when SV was administrated orally as an adjunct therapy to enhance current asthma therapies in asthmatic patients (11). This could be due to the lipophilic nature of SV and its rapid systemic clearance when taken orally resulting in low bioavailability and subsequent subtherapeutic levels of SV in the lung (12).…”
Section: Introductionmentioning
confidence: 99%
“…Although some minor improvements in intermediate endpoints have been noted in some trials, results have been mixed, and few trials have found meaningful effects on hard clinical outcomes. A recent systematic review of randomized controlled trials and observational studies of statins in asthma found no consistent statistically significant improvements in clinical or airway function outcomes [142], and a meta-analysis of randomized controlled trials found no significant improvement in spirometry [143]. That said, the trials to date have been relatively small and short-term, have not tested all statins on the market, and have been underpowered to properly test asthma subphenotypes (e.g., obese asthmatic, non-atopic asthmatic).…”
Section: Statins As Potential Therapeutics In Diseases Of Adaptive Immentioning
confidence: 99%